2011
DOI: 10.1080/09540121.2011.560930
|View full text |Cite
|
Sign up to set email alerts
|

Commercial sex venues, syphilis and methamphetamine use among female sex workers

Abstract: The objective of this study was to assess the factors associated with methamphetamine (MA) use, syphilis, and unprotected sex among female sex workers from different type of venues in Qingdao City, Shandong Province of China. Three consecutive cross-sectional surveys provided information on demographics, sexual and drug use behaviors, and HIV-related services. Of 1187 participants, 3.0% were infected with syphilis; 30.2% ever used MA; 58.3% ever had unprotected commercial sex in the past month. The prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 17 publications
4
22
1
1
Order By: Relevance
“…Research in China has also shown that the use of stimulants (amphetamines, methamphetamine) is increasing to epidemic levels (Commission). Recent studies have also linked stimulant use to Chinese female sex workers, HIV/STIs, and sex risks in China (Bao et al, 2012;Commission;Hong & Li, 2008;Kang et al, 2011;Liao et al, 2011;Liao et al, 2013). It is not clear if the current findings represent a trend of increasing stimulant use specific to Chinese MSM, if stimulant use in China is related to selling sex, or reflect the increases seen throughout China.…”
Section: Discussionmentioning
confidence: 53%
“…Research in China has also shown that the use of stimulants (amphetamines, methamphetamine) is increasing to epidemic levels (Commission). Recent studies have also linked stimulant use to Chinese female sex workers, HIV/STIs, and sex risks in China (Bao et al, 2012;Commission;Hong & Li, 2008;Kang et al, 2011;Liao et al, 2011;Liao et al, 2013). It is not clear if the current findings represent a trend of increasing stimulant use specific to Chinese MSM, if stimulant use in China is related to selling sex, or reflect the increases seen throughout China.…”
Section: Discussionmentioning
confidence: 53%
“…Our recent study revealed an alarmingly high prevalence of methamphetamine use among female sex workers in same cities of Shandong. 29,51,52 The relationship between drug use and bisexual activities as well as syphilis displayed in the present study underscored that Shandong's gay men might also face potential risks of emerging drug use, which might play a potentially significant role of bisexual behaviors in epidemiologic bridging.…”
Section: Liao Et Almentioning
confidence: 86%
“…Globally, high rates of sex trading behaviors have been observed among methamphetamine users (Couture et al, 2012; Kang et al, 2011; Rawstorne, Digiusto, Worth, & Zablotska, 2007; Semple, Strathdee, Zians, & Patterson, 2011; Shannon et al, 2011; Urada et al, 2014). In South Africa, 20 to 55% of methamphetamine users report that they have participated in sex trading (Meade et al, 2012; Pitpitan et al, 2014), and rates from other settings range from 26 to 43% (Semple, Strathdee, Zians, & Patterson, 2010; Semple et al, 2011).…”
Section: Introductionmentioning
confidence: 99%